The Effects of Service Quality and Additional Factors to Electronic Word of Mouth and Revisit Intention at Dental Clinics Mediated by Patient Satisfaction - Putri Kartika Dusak (Eduvest - Journal of Universal Studies, 2025)
The rapid growth of the dental industry, driven by increasing awareness of dental health through government and community health programs, has led to heightened competition among dental clinics across Indonesia. Clinics are adopting various strategies, such as improving service quality, modernizing equipment, and leveraging social media, to attract and retain patients. This study investigates the mediating role of patient satisfaction in the relationship between service quality, cost-effectiveness, staff-related factors, electronic Word of Mouth (eWoM), and revisit intention. Understanding these factors is critical for dental clinics to improve patient experiences, enhance satisfaction, and increase both patient revisit rates and positive eWoM, which serve as essential drivers of clinic success. The study highlights that empathy, dependability, and assurance in service quality significantly impact patient satisfaction, leading to stronger loyalty and advocacy. By focusing on these dynamics, dental clinics can improve service quality and competitiveness in Indonesia's evolving healthcare landscape, particularly in both urban and rural areas where market conditions and patient demands differ.